Coach-Athlete Relationship and Grit on Athletes with Disabilities - Andre Genta Senjaya; Charyna Ayu Rizkyanti; Andi Tenri Faradiba (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
This study was conducted to examine the correlation between the coach-athlete relationship and grit in athletes with disabilities. An overview of the coach athlete relationship using the CART-Q (Jowett and Ntoumanis, 2004) and grit using the Grit Scale (Duckworth, Peterson, Matthews and Kelly, 2007). Research participants consisted of 38 athletes with disabilities aged 16-48 years and were selected by purposive sampling technique. The results showed that there was a significant correlation r= 0.455 between the coach-athlete relationship and grit in athletes with disabilities. This Study are expected to be an evaluation of athletes, coaches and all National Paralympic Committee of Indonesia (NPCI) administrators to pay more attention to the quality of good relationships between coaches and athletes, while maintaining enthusiasm and perseverance in training and regular long-term matches in order to maintain sports achievements.